2017
DOI: 10.1002/ccd.27316
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of the Impella ventricular assist device for high‐risk percutaneous coronary interventions: A systematic review

Abstract: The Impella device was found to improve procedural and hemodynamic parameters, but only limited randomized data are available regarding clinical outcomes associated with its use. Large, multicenter RCTs are needed to definitively establish the effectiveness of the Impella device among high-risk PCI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…In our cohort protected by ECLS, the rate of renal failure, 12%, was slightly higher than in Flaherty's study, but still lower than the described unprotected rate. The main complication in our study cohort was bleeding requiring RBC transfusion, occurring in 49% of cases, which is considerably more frequent than in other prospective and retrospective cohorts described elsewhere 26 . Although anemia has been shown to be associated with adverse outcome in patients with acute coronary syndrome or patients undergoing PCI, numerous studies have demonstrated that RBC transfusion is independently associated with increased mortality and increased rate of major adverse cardiac events (MACE) in these patients 27‐32 .…”
Section: Discussionmentioning
confidence: 66%
“…In our cohort protected by ECLS, the rate of renal failure, 12%, was slightly higher than in Flaherty's study, but still lower than the described unprotected rate. The main complication in our study cohort was bleeding requiring RBC transfusion, occurring in 49% of cases, which is considerably more frequent than in other prospective and retrospective cohorts described elsewhere 26 . Although anemia has been shown to be associated with adverse outcome in patients with acute coronary syndrome or patients undergoing PCI, numerous studies have demonstrated that RBC transfusion is independently associated with increased mortality and increased rate of major adverse cardiac events (MACE) in these patients 27‐32 .…”
Section: Discussionmentioning
confidence: 66%
“…It is rapidly deployed and improves heart function in patients with acute CS but also for patients with chronic heart failure. They have proven to be safe, and effective at improving hemodynamic parameters when the heart is acutely decompensated [4]. The devices can be inserted with multiple approaches but also with different types of operators.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published systematic review reported the outcomes of controlled and uncontrolled studies of high-risk PCI with Impella 2.5-support, the majority being 30-day MACCE. [ 10 ] MACCE in the controlled studies ranged between 15% and 35% during a 30-day follow-up whereas uncontrolled studies demonstrated considerably lower 30-day MACCE between 5% and 20%. [ 12 14 , 25 27 ] Compared to intraaortic balloon pump, protected PCI with the Impella showed a trend toward lower MACCE after 90 days while there was no difference after 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 8 ] In this subset of patients, the temporary implantation of a peripheral ventricular assist device may improve short- and long-term outcomes. [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%